People analytics for dummies - West, Mike (Tantor Media, 2020)
Maximize performance with better dataDeveloping a successful workforce requires more than a gut check. Data can help guide your decisions on everything from where to seat a team to optimizing production processes to engaging with your employees in ways that ring true to them.People analytics is the study of your number one business asset-your people-and this book shows you how to collect data, analyze that data, and then apply your findings to create a happier and more engaged workforce.#9679 Start a people analytics project#9679 Work with qualitative data#9679 Collect data via communicationsIf your organization is ready to better understand why high performers leave, why one department has more personnel issues than another, and why employees violate, People Analytics For Dummies makes it easier.
Downloadable audio file
Keywords: Business; Affaires; businesses (business enterprises); BUSINESS & ECONOMICS / General; Downloadable audio books; Audiobooks; Livres audio